Noise minimization techniques for modulator demodulator circuits used for chopper stabilization in CMOS-MEMS sensor applications - Sutri, N.Y. (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper presents design, simulation and study of different noise minimization techniques that should be used in chopper stabilization circuits for CMOS-MEMS sensor readout interface circuit applications. Chopper stabilization technique is widely used in CMOS-MEMS sensors, as it is effective in tackling low frequency noises including the most dominant, flicker noise (1/f). In CMOS-MEMS sensors where noise is one of the main design targets, it is necessary to minimize noise arising from the chopper stabilization circuit itself to boost the overall noise performance. Chopper circuits contribute part of the total input referred noise and appropriate techniques need to be deployed in place to minimize the overall effect. Here in this work, different techniques which should be considered to reduce noise from the chopper circuits are discussed and analyzed. The demonstrated work is designed in MIMOS 0.35 Î¼m AMS CMOS 3.3 V CMOS process technology and Cadence Spectre circuit simulator is used to verify and analyze the circuit performances. Â© 2015 IEEE.